Financial Management Practices and Financial Wellbeing Among Regular Bank Employees in Polomolok, South Cotabato - Tiongco, Maricris S.; Miase, Alma Lyn S. (International Journal of Research in Interdisciplinary Studies, 2025)
In this study, the financial management practices and financial wellbeing of regular bank employees in Polomolok, South Cotabato were examined to find out whether certain financial management practices impacted their perceived financial wellbeing. The study looked at various financial management indicators, namely cash management, savings management, and maintaining personal budgets. The study was descriptive correlational in nature and collected data from 105 regular bank employees using a structured questionnaire. A Spearman Rank Correlation analysis found a very low positive but not statistically significant correlation (r = .176, p > .05) between financial management practices and financial wellbeing. Although developing good financial habits certainly helps, they are not the only predictors of financial wellbeing. The study concluded that they will always be other variables that likely play a larger role in influencing financial wellbeing than financial management practices; i.e. external macroeconomic conditions (e.g., inflation, employment levels) and unanticipated life events. Although regular bank employees demonstrate generally knowledgeably and disciplined financial management practices, more informed targeted assistance would help develop their personal budgeting. The research made recommendations for bank management to offer some financial wellness programs, academic institutions to enhance their curriculum in financial management, and additional research to identify external variables which may impact financial wellbeing.